Justification of the Possibility of Using Cold-Plasma Method in Surgery of Papillomatosis and Dupuytren’s Contracture; Micro/Nanotechnologies and Electron Devices (EDM) - Zhumantaeva N. A. Nabat Abdesenovna; Lisitsyna L. A. Liliya Ivanovna; Pedder V. V. Valery Viktorovich; Aleinik A. N. Aleksandr Nikonorovich; Kondrashov A. Y. Aleksandr Y. (2015, 2015)
Title screen